Potential Prognostic Value of a Seven m6A-Related LncRNAs Signature and the Correlative Immune Infiltration in Colon Adenocarcinoma - Chai, Xiu-kun; Qi, Wei; Zou, Chun-Yan; He, Chen-Xi; Su, Miao; Zhao, Dong-Qiang (Frontiers in Genetics, 2021)
Colorectal cancer (CRC) ranks third in incidence and second in mortality from cancer-related death worldwide. Nevertheless, prognostic evaluation and treatment effect of colon adenocarcinoma (COAD) are unsatisfactory. Thus, the finding of novel prognostic markers and therapeutic drug targets for COAD is crucial. In recent years, research on the relationship between m6A methylation and lncRNA in tumors has become a hotspot. However, studies on COAD remain elusive. We downloaded the COAD gene expression from TCGA. By co-expression analysis, Lasso Cox regression analysis, univariate and multivariate Cox regression, we constructed an independent prognostic signature of seven m6A-related lncRNAs. The prognostic lncRNAs were divided into 2 clusters, as well as into two groups of low-high risk. We obtained the results below: First, cluster 2 had a higher risk score with a lower survival rate; the risk score was higher in groups with advanced clinical features, such as stage III-IV, N1-3, and M1. Second, in particular, the expression of AC156455.1 was notably increased in tumor tissues and cluster 2, and the lncRNA ZEB1−AS1 was significantly higher in the high-risk group, suggesting they may be further studied for specific prognostic value. Third, five types of immune cells showed differences in two clusters, and three kinds of the cells were upregulated in cluster 2, which had a low survival rate. The expression of memory B cells was positively correlated with the risk score. Thus, the signature may predict the prognosis of COAD, which is also closely associated with immune cell infiltration, and new therapeutic targets can be explored from this field.